RANCANG BANGUN SISTEM MONITORING DAN PENGENDALIAN LINGKUNGAN RUANG KELAS BERBASIS IOT MENGGUNAKAN ESP32 - Yusuf Sihombing; Biondi Sitompul; Dicki C Manurung; Eka Dodi Suryanto; Dian Putra Saragi (JOURNAL SAINS STUDENT RESEARCH, 2026)
Classroom environmental conditions play an important role in supporting the comfort and effectiveness of the teaching and learning process. Parameters such as temperature, humidity, light intensity, and air quality directly affect students’ concentration, health, and productivity. This study aims to design and implement an Internet of Things (IoT)-based monitoring and control system for classroom environments using the ESP32 microcontroller. The proposed system integrates multiple sensors, including DHT22 for temperature and humidity, LDR for light intensity, and MQ-2 for air quality detection. Data collected from the sensors are processed by ESP32 and transmitted in real-time to an IoT platform for remote monitoring, while also displayed locally on an LCD. The system employs an ON–OFF control method to automatically regulate devices such as fans, lamps, exhaust fans, and humidifiers based on predefined threshold values. The results show that the system is capable of monitoring environmental parameters accurately and responding automatically to changes in real-time conditions. The integration of monitoring and control functions in a single IoT-based system provides an effective and efficient solution for improving classroom environmental quality. This system can be further developed as part of a smart classroom concept to enhance learning comfort and environmental management.